DINAMIKA KEGIATAN KEIRIGASIAN DAN PERUBAHAN SOSIAL MASYARAKAT PETANI DI DESA PLERET, KECAMATAN PLERET, KABUPATEN BANTUL - Teguh Kismantoroadji (Jurnal Dinamika Sosial Ekonomi, 2007)
Conflict among water users such as farmers and rural institutions costumarily emerged as a consequence of limited supply of irrigation. This paper provides an anatlytical frame-work consequence for irrigation management institutions to solve the emerging conflicts and to provide foundation for irrigation system management. The proposed foundation incdudes the empowerment of water user associations to undertake larger responsibility through collective approach in the form of federations. Beside the factors such as transparency and accountability, the irrigation management should also consider the institutional elements such as jurisdictional boundary, water rights, and rules of representation in solving the conflicts of water allocation.Keywords: Irrigation management, social institutional, jurisdictional boundary, water right, rules of representation